PATH-21. TELOMERE LENGTH ANALYSIS OF CNS TUMORS IN THE PEDIATRIC BRAIN TUMOR ATLAS. (4th December 2020) - Rokita, Jo Lynn; Gaonkar, Krutika; Ijaz, Heba; Miller, Daniel; Karras, Tasso; Santi, Mariarita; Martinez, Daniel; Koptyra, Mateusz; De Raedt, Thomas; Mason, Jennifer; Appert, Elizabeth; Lilly, Jena; et al.
Abstract: Subsets of pediatric cancers, including high grade glioma (pHGG), have high rates of uniquely long telomeres, associated with ATRX gene mutations and alternative lengthening of telomeres (ALT). Ultimately, these cancers may benefit from a therapy stratification approach. In order to identify and further characterize pediatric brain tumors with telomere lengthening (TL), we determined the intratelomeric content in silico from paired WGS of 918 tumors from CBTTC Pediatric Brain Tumor Atlas (PBTA). The results were highly concordant with experimental assays to determine ALT in a subset of 45 pHGG tumors from the set. Overall, 13% of the PBTA cohort had telomere lengthening. We confirmed the highest rate of TL (37%) in the pHGG cohort (37/100 tumors; 30/82 patients). There was no statistical difference in age, gender or survival in subset analysis. As expected, the patient pHGG tumors with telomere lengthening were enriched for ATRX mutations (60%, q= 1.76e-3). However, 6 tumors without ATRX mutation also had normal protein expression, suggesting a different mechanism of inactivation or TL. The pHGG tumors with telomere lengthening had increased mutational burden (q=8.98e-3) and included all known pHGG cases (n=6) in the cohort with replication repair deficiencies. Of interest, the second highest rate of telomere lengthening was 9 subjects (24%) in the craniopharyngioma cohort. None of the craniopharyngioma tumors had ATRX mutations or low ATRX expression, and 55% of those with TL had CTNNB1 mutations. Finally, lower rates of telomere lengthening were found in medulloblastoma (10%), ependymoma (10%), low grade astrocytoma (8%) and ganglioglioma (7/47, 15%).